Quality of life of People Living with HIV/AIDS - Harnlakorn, Pornnipa; Rattanamanee, Somjai; Khanthong, Prakob (วารสารพยาบาลศาสตร์และสุขภาพ, 2012)
This descriptive study aimed to study the quality of life and factors related quality of life of people livingwith HIV/AIDS (PWAs). The subjects were PWAs at the infectious clinic, Out-patient department in Srinagarindhospital, Faculty of Medicine, Khon Kaen University. A sample of 113 PWAs was purposively selected.Research instruments included demographic data form and quality of life questionnaires (Ferrell et al., 1995).Data were collected during January 1 to December 30, 2009 and analyzed using descriptive statistics, Pearsonûsproduct moment correlations and Stepwise multiple regression. Results revealed that the majority of the subjectshave the total score of quality of life were in moderate level, also, physical and spiritual well-being score werein high level and psychosocial and social well-being were in moderate level. The factors related quality of lifewere CD4, staging and duration receiving antiretroviral therapy. Both CD4 and staging can jointly predict thevariance of the quality of life 71.9%.